GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 646566 species occurrences available in GBIF matching the query: DatasetKey: Floristic Databases of Mecklenburg-Pomerania - Higher Plants. The dataset includes 646566 records from 1 constituent datasets: 646566 records from Floristic Databases of Mecklenburg-Pomerania - Higher Plants.
Keywords: GBIF; biodiversity; species occurrences